Potentially zoonotic pathogens and parasites in opportunistically sourced urban brown rats (Rattus norvegicus) in and around Helsinki, Finland, 2018 to 2023 - Aivelo, Tuomas; Alburkat, Hussein; Suomalainen, Nina; Kukowski, Rebekka; Heikkinen, Petra; Oksanen, Antti; Huitu, Otso; Kivistö, Rauni; Sironen, Tarja (Publications Office, 2024)
Background Brown rats (Rattus norvegicus) are synanthropic rodents with worldwide distribution, which are known to harbour many zoonotic pathogens and parasites. No systematic zoonotic surveys targeting multiple pathogens and parasites have previously been conducted in urban rats in Finland. Aim In Helsinki, Finland, we explored the presence and prevalence in brown rats of certain pathogens and parasites (including helminths, viruses and bacteria) across potentially zoonotic taxa. Methods We opportunistically received rat carcasses from pest management operators and citizens from 2018 to 2023. We searched for heart- or lungworms, performed rat diaphragm digestion to check for Trichinella and morphologically identified intestinal helminths. We assessed virus exposure by immunofluorescence assay or PCR, and detected bacteria by PCR (Leptospira) or culture (Campylobacter). Results Among the rats investigated for helminths, no heart- or lungworms or Trichinella species were detected and the most common finding was the cestode Hymenolepis nana (in 9.7% of individuals sampled, 28/288). For some of the surveyed virus taxa, several rats were seropositive (orthopoxviruses, 5.2%, 11/211; arenaviruses, 2.8%, 6/211; hantaviruses 5.2%, 11/211) or tested positive by PCR (rat hepatitis E virus, 1.8%, 4/216). Campylobacter jejuni (6.6%, 17/259) and Leptospira interrogans (1.2%, 2/163) bacteria were also present in the rat population examined. Conclusions Prevalences of potentially zoonotic pathogens and parasites in brown rats in Helsinki appeared low. This may explain low or non-existent diagnosis levels of rat-borne pathogen and parasite infections reported in people there. Nevertheless, further assessment of under-diagnosis, which cannot be excluded, would enhance understanding the risks of zoonoses.
Keywords: brown rats; Rattus norvegicus; Helsinki; Finland